The Paradox of the Christian Life: Paul as the Wretched Man in Romans 7:14-25 - Burgos, Michael (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2021)
Romans 7:14-25 is a crucial component of Paul’s greater argument in Romans 6-8. This periscope exemplifies the embattled Christian life and the paradoxical experience of living as a justified sinner. A litany of commentators has asserted that Romans 7:14-25 does not depict the Christian experience but the experience of Paul before his conversion. This study summarizes the argument of Romans 6-8 and identifies the most significant evidence for a post-conversion reading of Romans 7:14-25. Using simple hermeneutical tools of interpreting the text under review, the paper opines that, the main objections to a post-conversion reading should be maintained as it is being articulated and addressed herein.